Experimental exposure of male volunteers to N-methyl-2-pyrrolidone (NMP): acute effects and pharmacokinetics of NMP in plasma and urine. Issue 4 (April 1997) - Akesson, B; Paulsson, K
Abstract : OBJECTIVES: To study the acute effects of exposure to the increasingly used solvent, N-methyl-2-pyrrolidone (NMP) in male volunteers. Further, to determine the NMP concentration in plasma and urine during and after the exposure. METHODS: Six male volunteers were exposed for eight hours on four different days to 0, 10, 25, and 50 mg/m3 NMP. Plasma was collected and urine was sampled during and after the exposure. Changes in nasal volume were measured by acoustic rhinometry and in airway resistance by spirometry. RESULTS: The eight-hour experimental exposure to 10, 25, and 50 mg/m3 did not induce discomfort to eyes or upper airways. Acute changes in nasal volume were not found, and no changes in the spirometric data could be registered. The elimination curves suggested a non-linear pattern and at the end of exposure showed mean (range) half lifes of NMP in plasma of about 4.0 (2.9-5.8) hours and in urine 4.5 (3.5-6.6) hours. The unmetabolised NMP found in urine samples collected during exposure and at the subsequent 44 hours corresponded to about 2% of the calculated absorbed dose. At the end of the exposure there was a close correlation between exposures and the plasma concentration and urinary excretion of NMP. CONCLUSIONS: NMP was absorbed through the respiratory tract and readily eliminated from the body, mainly by biotransformation to other compounds. Exposure to 10, 25, or 50 mg/m3 NMP did not cause nose, eye, or airway irritation. Thus, NMP is a mild irritant.